2000
DOI: 10.1063/1.126824
|View full text |Cite
|
Sign up to set email alerts
|

Growth of zinc blende MgS/ZnSe single quantum wells by molecular-beam epitaxy using ZnS as a sulphur source

Abstract: Zinc blende MgS has been grown on GaAs by molecular beam epitaxy using a novel method where the sources were Mg and ZnS. A reaction at the surface results in the formation of MgS layers with a Zn content estimated by secondary ion mass spectrometry and Auger spectroscopy to be between 0.5% and 2%. Double crystal x-ray rocking curve measurements of ZnSe/MgS/ZnSe layers show layers with good crystallinity. Using this growth technique layers up to 67 nm thick have been grown. Photoluminescence measurements of MgS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 10 publications
6
48
1
Order By: Relevance
“…Trends in the series BeO through BaO [10] and BeS through BeTe [15,19,23] were described. BeS [6,9,12,17] and MgS [25,33,40] represent materials worth mentioning. Not only closed-shell parent systems, but also radical-ions [13,14,27a,29,35,36] derived from them were subjects of studies, sometimes by means of photoelectron spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Trends in the series BeO through BaO [10] and BeS through BeTe [15,19,23] were described. BeS [6,9,12,17] and MgS [25,33,40] represent materials worth mentioning. Not only closed-shell parent systems, but also radical-ions [13,14,27a,29,35,36] derived from them were subjects of studies, sometimes by means of photoelectron spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group has demonstrated that a simple modification to the MBE growth process can be used to grow much thicker layers of both MgS [12,13] and MnS [14] in the ZB structure. In this paper, we review the growth process and subsequently describe some results obtained from structures containing both MgS and MnS.…”
mentioning
confidence: 99%
“…• C allows one to grow MgS layers of necessary thickness without transformation to a rock-salt phase [6].…”
Section: Methodsmentioning
confidence: 99%
“…The middle of the stop-band was chosen to correspond to a standard ZnCdSe QW wavelength, which is ≈ 520 nm. It has been pointed out by Bradford et al [6] that pseudomorphic growth of zinc-blende MgS on GaAs is only possible under low temperatures and is limited by a certain critical thickness depending on the temperature. These constraints do not allow growing of a pure MgS/ZnSe DBR with λ/4-thick layers.…”
Section: Bragg Mirror Designmentioning
confidence: 99%
See 1 more Smart Citation